Cervical Vertebral Artery to Facial Branch External Carotid Artery Bypass: 2-Dimensional Operative Video. Issue 6 (6th March 2020) - Hendricks, Benjamin K; Spetzler, Robert F
Abstract: Posterior circulation ischemia often presents with dizziness, ataxia, visual disturbances, or motor-sensory deficits. The vertebral artery stenosis most frequently involves the V1 segment proximal to the foraminal segment. This patient demonstrated critical stenosis of the left V1 segment of the vertebral artery related to atherosclerotic disease. A left cervical dissection was performed, and the cervical transverse foramen was opened to permit exposure of the vertebral artery in the V2 segment. The vertebral artery was proximally occluded and transected. An endarterectomy was performed, and an end-to-end anastomosis of the facial branch of the external carotid artery to the distal segment of the transected vertebral artery was completed. Indocyanine green angiography was used to confirm patency of the anastomosis. The patient gave informed consent for surgery and video recording. Institutional review board approval was deemed unnecessary. Used with permission from Barrow Neurological Institute, Phoenix, Arizona .